Is Modern Technology Responsible for Jobless Recoveries? - Georg Graetz; Guy Michaels (Institute of Labor Economics (IZA), 2017)
Since the early 1990s, recoveries from recessions in the US have been plagued by weak employment growth. One possible explanation for these "jobless" recoveries is rooted in technological change: middle-skill jobs, often involving routine tasks, are lost during recessions, and the displaced workers take time to transition into other jobs (Jaimovich and Siu, 2014). But technological replacement of middle-skill workers is not unique to the US it also takes place in other developed countries (Goos, Manning, and Salomons, 2014). So if jobless recoveries in the US are due to technology, we might expect to also see them elsewhere in the developed world. We test this possibility using data on recoveries from 71 recessions in 28 industries and 17 countries from 1970-2011. We find that though GDP recovered more slowly after recent recessions, employment did not. Industries that used more routine tasks, and those more exposed to robotization, did not recently experience slower employment recoveries. Finally, middle-skill employment did not recover more slowly after recent recessions, and this pattern was no different in routine-intensive industries. Taken together, this evidence suggests that technology is not causing jobless recoveries in developed countries outside the US.
Keywords: E32; J23; O33; 330; job polarization; jobless recoveries; routine-biased technological change; robots